THE INFLUENCE OF BRAND AWARENESS, BRAND IMAGE AND E-SERVICE QUALITY ON PURCHASING DECISIONS IN LAZADA E-COMMERCE THROUGH PURCHASE INTENTION AS AN INTERVENING VARIABLE - Inge Lisnawati; Ditiya Himawati; Septi Mariani Tis’a Ramadhani (Jurnal Ilmiah Ekonomi Bisnis, 2025)
The increasingly rapid advances in technology and the internet have influenced various human activities and activities, including electronic commerce or e-commerce transactions. This research aims to determine and analyze the direct and indirect influence of brand awareness, brand image, and e-service quality on decisions through purchasing intention in Lazada e-commerce. This research uses primary data obtained from an online questionnaire in the form of a Google form, which was distributed to 150 respondents. Respondents are Lazada e-commerce users who are over 17 years old and live in the Jabodetabek area. This research uses PLS-SEM analysis, which consists of a measurement model (outer model), a structural model (inner model), and a model goodness-of-fit test (model fit). The results of this research show that brand awareness, brand image, and e-service quality have a direct and indirect influence on purchasing decisions through purchase intention in Lazada e-commerce.